2009
DOI: 10.1007/s11033-009-9742-9
|View full text |Cite
|
Sign up to set email alerts
|

The chromosomal localization, expression pattern and polymorphism analysis of porcine FSCN1 gene differently expressed from LongSAGE library

Abstract: Fascin homologue 1 (FSCN1) has established roles in cell adhesion, motility, and cell-cell interactions. Our LongSAGE analysis suggested that FSCN1 was potentially differentially expressed in prenatal pig skeletal muscle. We have cloned the genomic DNA and mRNA sequence of FSCN1 gene and mapped it to SSC3p16-p17. The FSCN1 gene was differently expressed during prenatal skeletal muscle development and exhibited different expression pattern between Tongcheng and Landrace pigs. In Tongcheng pigs, FSCN1 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The previous studies showed that the establishment of the total number of fibers involves two major waves of fiber generation: primary muscle fiber formation at 35-60 dpc and secondary muscle fibers assembled at 54-90 dpc 37-39, the expression patterns of OLFML3 gene during prenatal skeletal muscle development in our study indicating that it mainly involved in the formation of primary muscle fibers. The differential expression patterns from Landrace to Tongcheng pigs also showed that there are developmental synchronizations in prenatal skeletal muscle development between the two pig breeds, the result was consistent with our previous report 31, 40, which concluded Landrace pigs may have a quicker muscle growth rate than Tongcheng pigs. Prenatal muscle development programs postnatal performance.…”
Section: Discussionsupporting
confidence: 91%
“…The previous studies showed that the establishment of the total number of fibers involves two major waves of fiber generation: primary muscle fiber formation at 35-60 dpc and secondary muscle fibers assembled at 54-90 dpc 37-39, the expression patterns of OLFML3 gene during prenatal skeletal muscle development in our study indicating that it mainly involved in the formation of primary muscle fibers. The differential expression patterns from Landrace to Tongcheng pigs also showed that there are developmental synchronizations in prenatal skeletal muscle development between the two pig breeds, the result was consistent with our previous report 31, 40, which concluded Landrace pigs may have a quicker muscle growth rate than Tongcheng pigs. Prenatal muscle development programs postnatal performance.…”
Section: Discussionsupporting
confidence: 91%
“…FSCN1 is an actinbinding protein critical to cell adhesion, cell motility, and cellcell interactions. In normal prenatal pig skeletal muscle, FSCN1 expression increases during major muscle developmental spurts, but postnatally it is expressed highly only in brain tissues during accelerated neural cell development [133] . The CREB pathway is often activated in different metastatic human cancers, causing the upregulation of FSCN1 expression [134] .…”
Section: Cell Factors Deregulated In Cancer By Myomirsmentioning
confidence: 99%
“…Fascin-1 is abundant early in development, especially in the central nervous system (CNS) and migrating cells, and is then downregulated as cells mature (De Arcangelis et al, 2004; Zhang et al, 2008; Zanet et al, 2009; Tang et al, 2010). In this paper, ‘fascin’ refers to the product of the Fascin-1 genes ( FSCN1 in humans, MIM#602689; Fscn1 in mouse; and singed in Drosophila , FBgn0003447).…”
Section: Introductionmentioning
confidence: 99%